2019
DOI: 10.1186/s12913-019-4533-z
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors’ experiences of team support along their recovery continuum

Abstract: BackgroundA coordinated stroke rehabilitation care team is considered optimal for supporting stroke survivors from diagnosis to recovery. Despite this recognition, many stroke survivors cannot access essential rehabilitation services. Furthermore, there is a lack of understanding of stroke patients’ and their caregivers’ rehabilitation needs and wishes. We sought to gain insight into healthcare and social structures from the perspective of patients and caregivers that can better support long-term stroke recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 31 publications
3
55
0
6
Order By: Relevance
“…The three qualitative studies exploring this aspect of interventions [ 29 , 33 , 34 ] consistently identified the benefits of involving carers or families in the group sessions such as informational exchange and support. This is supported by past research [ 48 ], which identified such support as essential. Further research is required to consider the impact of the intervention on mood states, as changes have been identified across other chronic illnesses [ 23 ].…”
Section: Discussionsupporting
confidence: 77%
“…The three qualitative studies exploring this aspect of interventions [ 29 , 33 , 34 ] consistently identified the benefits of involving carers or families in the group sessions such as informational exchange and support. This is supported by past research [ 48 ], which identified such support as essential. Further research is required to consider the impact of the intervention on mood states, as changes have been identified across other chronic illnesses [ 23 ].…”
Section: Discussionsupporting
confidence: 77%
“…13,14 After transient ischemic attack or minor stroke, the risk of consequent stroke is lower for patients treated by services that provide emergency intervention using a multidisciplinary approach. 15 Our results showed that in only approximately two-thirds of our studied hospitals, patients with stroke symptoms were most likely to be admitted to the ICU in the first 72 h, only 35.14% of hospitals had arrangements with a local ambulance.…”
Section: Limitations Of the Acute Stroke Servicesmentioning
confidence: 61%
“…The importance of addressing post-stroke psychosocial needs is emphasized [13][14][15]. Persons with stroke themselves miss integrated strategies to prevent psychosocial problems [10,11,[16][17][18] and express disappointment at how health care professionals meet their individual needs and expectations during the rehabilitation process [5,11,13,16,19]. However, even though health care personnel are aware of the importance of addressing psychosocial needs during rehabilitation, there is still little evidence that these needs are systematically addressed in stroke rehabilitation [13,15].…”
Section: Introductionmentioning
confidence: 99%